If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 3 + 5m + -6p = 0 Reorder the terms: 3 + N + 5m + -6p = 0 Solving 3 + N + 5m + -6p = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + N + 5m + -3 + -6p = 0 + -3 Reorder the terms: 3 + -3 + N + 5m + -6p = 0 + -3 Combine like terms: 3 + -3 = 0 0 + N + 5m + -6p = 0 + -3 N + 5m + -6p = 0 + -3 Combine like terms: 0 + -3 = -3 N + 5m + -6p = -3 Add '-5m' to each side of the equation. N + 5m + -5m + -6p = -3 + -5m Combine like terms: 5m + -5m = 0 N + 0 + -6p = -3 + -5m N + -6p = -3 + -5m Add '6p' to each side of the equation. N + -6p + 6p = -3 + -5m + 6p Combine like terms: -6p + 6p = 0 N + 0 = -3 + -5m + 6p N = -3 + -5m + 6p Simplifying N = -3 + -5m + 6p
| 61+(10x-4)=(16x+9) | | 5x+12-3x=-2x-13 | | -2x=21 | | 5+-2(x+6)=14 | | 61+(10x-4)-(16x+9)=180 | | 5x+12-3x=2x-13+x | | (x^2-6x+5)(x^2-3x-10)= | | 6x+11=-2x+29 | | g(x)=x^2+-20 | | 3x-29=x-30 | | (x+29)+(2x-5)+x=180 | | 4x+9y=36solvey | | F(x)=x^4+64x | | 2(x)+2(2x-3)=72 | | 3L+3(L-5)=141 | | 8x-3=7(x+2)+3 | | 4x-6=3(x-10)-4 | | 4(5x+15)=40 | | 5x+4=4(x+6)+3 | | 4w+8-w=2w-2+9 | | f(x)=4x^2-64 | | h=5(3.14)m | | 2(5x+35)=30 | | 5y-2(21)=3 | | -2y+-2+5y=3y+3-2 | | 3(x-6)-3=25x-87 | | 9.1x-5.2= | | y=16-4x | | 2+2=4*2+2 | | 2(5x+15)=40 | | -0.10(21)+0.60x=0.05(x-20) | | 32-3x=200 |